Pengaruh Kompensasi, Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Pegawai Camat Talawi - Masrisal Masrisal; Tun Huseno (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
Today every government organization is expected to improve the performance of its employees in order to provide the best service to the community. To achieve this goal, human resources are needed who have skills in accordance with their respective fields. Likewise, the object of research carried out at the Talawi District Office. he purpose of this study was to determine how big the influence of compensation, leadership and organizational culture on the performance of Talawi sub-district employees to all 30 employees. This research was conducted by distributing questionnaires and conducting interviews and observations. Then the data is processed using the SPSS (Statistical Program For Social Science) analysis technique.The results showed that compensation had a positive effect on employee performance with X1 of 0.144, leadership had a positive effect on performance with X2 of 0.014, and work culture had a positive effect on performance with X3 of 0.945.